‘Political imagination, in its most fervid and patriotic flights’: Copyright and Constitutional Theory in Post-Confederation Canada - Miller, Bradley (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2009)
AbstractThis article is about differing ideas of self-government in post-Confederation Canada. It looks in particular at how the issue of copyright exposes a provocative and little-understood strain of constitutional theory in the first few decades of Confederation. This theory contended that the British North America Act was far more than a division of powers within a still-subordinate colony of the empire. Instead, proponents of the theory argued that the act was a constitutional turning point which transferred a share of British sovereignty to Canada, and gave the dominion new power even to contravene imperial law. This theory found support among many prominent politicians, judges, lawyers, and scholars. Armed with this idea, the federal Parliament passed a bill in 1872 that would have overridden imperial copyright. But neither the bill nor the theory succeeded. Britain blocked the legislation and an emerging consensus among constitutional thinkers, lawyers, and judges rejected its theoretical underpinnings. By exploring the debate over the limits of Canada’s power, this paper points to the diversity of ideas that surrounded even the basic precepts of the constitutional order after 1867.